FEED ENRICHMENT WITH FISH OIL AND CORN OIL TO INCREASE EEL GROWTH RATE Anguilla bicolor (McCelland, 1844) - Sari, Dewi Retno; Tarsim, Tarsim; Hudaidah, Siti (University of Lampung, 2019)
Eel (Anguilla bicolor) is an Indonesian freshwater commodity that has high economic value but has slow growth. One method to accelerate eel growth is through feeding with the enrichment of essential fatty acids. The aim of this research is to know the increase of growth rate of eel fish fed with the enrichment of essential fatty acids with fish oil and corn oil. The study used 3 treatments and 3 replications ie A (0% corn oil + 0% fish oil), B (1.5% corn oil + 1.5% fish oil), and C (3% corn oil + 3% fish oil). Parameters observed included specific growth rate, total feed consumption, feed efficiency, fat retention, and survival rate. The supporting parameter is water quality. The data obtained were analyzed by analysis of variance and continued by fisher test with 95% confidence interval. The results showed that there was a significant effect (P <0.05) on the growth rate of eel fish fed with the enrichment of essential fatty acids with fish oil and corn oil. Treatment C (3% corn oil + 3% fish oil) is the optimum dose because it has the best growth performance and best feed efficiency that is specific growth rate (4.67%), total feed consumption (262,9 g), feed efficiency (61% ), fat retention (2.805%), and survival rate (80%).